Von Göttern und Gesteinen. Zur Interpretation dreier bemerkenswerter Kultobjekte im Tempel von Tôd - Lieven, Alexandra von (Zeitschrift für ägyptische Sprache und Altertumskunde, 2013)
In the scene 284 II in the crypts of the temple of Tôd, there is a unique depiction of three hippopotamus-like lumps of jasper. Up to now their strange iconography has eluded an explanation. In this paper, it is argued that indeed these were mere lumps of stone of peculiar shape, into which the Egyptians “saw” hippopotamuses. To back this interpretation up, other examples of similar cases of religious interest in odd-shaped stones or the like are presented. Finally, it is discussed why these “hippopotamuses” were believed to be forms of Tjenenet, as the inscriptions clearly state, when otherwise this goddess is not attested to have been associated with this kind of animal.